Novas sensibilidades culturais, novos mercados: representações sobre idosos na imprensa de negócios brasileira - Soulé, Fernanda Veríssimo (2016)
The aim of this study was to analyze the concepts of old age that have been spread by the economics and business media in the context of increasing longevity of the Brazilian population. The analysis of the production of cultural frames regarding age reveals that a notion generally taken as purely natural is actually a historical and social construction. Shifts in cultural perceptions of age have changed the economic space and also contributed to the diffusion of new understandings about it. Drawing on the Reflexive Sociology of Bourdieu and taking as references works of Economic Sociology, Sociology of Generations, Gerontology and Anthropology of Aging, the economic sphere and the markets were taken as social constructions. The statements produced by the magazines Exame and Pequenas Empresas Grandes Negócios (Small Companies, Big Businesses - PEGN) between 1990 and 2014 were analyzed based on the content analysis technique proposed by Bardin (1979). Old age represented in these magazines intend to sensitize two specific economic characters: the executive, in the case of Exame, and small business owners in the case of PEGN. In this sense, it was revealed the themes, terms, ideas, markets, organizations, people, authors, among other issues, to which they appealed to trigger identities associated with old age in their audience. First, each magazine was analyzed individually and then in a more aggregated way. Four ideas dominate the media space analyzed: planning for retirement; the domination of the economic logic to think about old age; the aging population and its macro and micro-economic impacts and; aspects related to boundaries and generational disputes. In general, publications analyzed alternate between the micro level, where each individual is responsible for his old age, and the macro level, dealing with the State and demographic changes. Old age is proposed as a privileged moment of fulfillment of dreams postponed during other phases of life. This emerging notion clashes with other more negative, that consider old age as a source of misery or expense, creating barriers to its reframing. Besides, the representations of generational issue turn out to be limited by orthodoxy, as in the case of the pension systems for retirement, in which it is reinforced the capitalization logic rather than the pay-as-you-go one. These ideas promote an individualized conception of old age instead of proposals that evoke an intergenerational solidarity.